Animal protein as a source of unidentified growth factors for swine - B A Koch; G Cowman; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1968)
Most authorities agree that the value of a protein source is determined by its content of essential amino acids. On that basis soybean meal compares favorably' with the other commonly fed animal protein sources. However, there is some evidence, especially in the poultry research literature, that certain animal protein sources may contain unidentified growth factors. This report describes a trial in which two different animal proteins were fed at the 5% level in place of soybean meal in growing finishing-swine rations.; Swine Day, Manhattan, KS, September 26, 1968
Keywords: Swine day; 1968; Swine; Animal protein; Growth; Finishing-swine rations